O papel do circuito hipocampo ventral - córtex pré-frontal medial na memória de reconhecimento e espacial (recente e remota) de ratos wistar - Crestani, Ariela Maltarolo (Universidade Federal de São Carlos, 2020)
The medial prefrontal cortex (mPFC) and the hippocampus (HPC) have well-established roles in processing memories. Ventral portion of the HPC (vHPC) and mPFC have reciprocal connections and seems to be involved with processing recent memories (HPC) and consolidating into remote cortical memories. Recent discoveries demonstrate the existence of functional lateralization of the mPFC associated with modulation of anxiogenic states and decision making. Yet, little is known about the possible lateralization of the mPFC and HPC as memory modulator. So, present work aimed to evaluate the involvement of the HPC-mPFC circuit in processing memory in behavioral paradigms, and to verify the possible functional lateralization of its individual parts and the circuit. Therefore, experiments with bilateral, right or left HPCv (experiment I), CPFm (experiment II) and HPC-CPFm circuit (experiment III) were carried out in rats submitted to the Morris Water Maze (MWM), object recognition and T-maze, to assess recent and remote memory. Data revealed that none of the experimental groups showed impaired locomotion, and recognition memory was intact regardless of experimental manipulation. vHPC injuries did not affect the animals' performance in spatial trainings in the MWM or the ability to recall recent memories; however, animals with bilateral vHPC lesion had impaired remote memory recall. No deficit was observed in T-maze, regardless of vHPC lesion. In experiment II; animals acquired spatial navigation in MWM and recalled recent memories, regardless of the injury. Any lesion in mPFC compromised animal’s ability to recall remote memories in MWM, whereas still evoked newly acquired memories. mPFC lesions (uni or bilateral) impaired animal’s performance in T maze. Finally, results from experiment III indicated that ipsilateral lesion (right or left) of HPC-mPFC circuit impaired the animals' performance even during acquisition phase in MWM and the recall of recently and remotely acquired memories in the same paradigm. Also, acquisition of spatial information in T maze were impaired. No evidence of lateralization was shown. Thus, HPC-CPFm pathway seems to be essential for processing spatial memories. Still, HPC showed involvement in recalling remote memories; whereas acquisition of new memories and recall of newly acquired memories were not affected when CPFm was preserved. CPFm presented the same responses pattern as HPC when assessing spatial memory in LAM; however, it seems to be a key structure in tasks involving decision making and reinforced behaviors; since lesion only in this region led to impairments in T maze.
Role of the hippocampus - medial pre-frontal cortex in recognition and spatial (recent and remote) memory of wistar rats
Keywords: Memória episódica; Memória recente; Memória remota; Hipocampo ventral; Córtex pré-frontal medial; Lateralização funcional; Episodic memory; Recent memory; Remote memory; Ventral hippocampus; Medial pre-frontal cortex; Functional lateralization; CIENCIAS BIOLOGICAS::FISIOLOGIA